BIOINTENSIVE MANAGEMENT OF WHITE GRUBS WITH BOTANICAL EXTRACTS IN INDIGENOUS COW (HARIANA) URINE - Rani, Puja; Thakur, Yogeeta; Sharma, Anupam; Sharma, Ashwani; Chandla, V. K. (Potato Journal, 2013)
Efficacy of plants viz. Azadirachta indica L., Sapindus mukorossi L., Chrysanthemum cinerariaefolium L., Nerium oleander L., Jatropha curcas L., Urtica diocia L. and Vitex negundo L. extracted in indigenous cow (Hariana) urine and used @ 5 ml/ litre was tested in the field trials during 2007 and 2008 to control white grub, Brahmina coriacae (Hope). All the extracts were effective in reducing the grub population as well as per cent tuber damage. The minimum per cent tuber damage in terms of number of tubers and weight of tubers was recorded in the treatment with indigenous cow (Hariana) urine extract of A. indica and Jatropha sp. in both the seasons.